Vibronic emissions between the X 1Σ+, A 1Π, C 1Σ−, D 1Δ, and E 1Σ+ states of silicon monoxide. (October 2019) - Feng, Yanan; Zhu, Zunlue
Highlights: Lifetimes are of the order of 10 ns for the A 1 Π and E 1 Σ + states. A 1 Π–X 1 Σ + and E 1 Σ + –X 1 Σ + transitions are strong. E 1 Σ + –A 1 Π, A 1 Π–D 1 ∆, and A 1 Π–C 1 Σ − transitions are weak. Radiative lifetime slowly increases as the J increases for the A 1 Π state. Radiative lifetime is almost constant for any J of the E 1 Σ + state. Abstract: The potential energy curves of the X 1 Σ +, A 1 Π, C 1 Σ −, D 1 Δ, and E 1 Σ + singlet states of silicon monoxide are calculated using the complete active space self-consistent field method, followed by the valence internally contracted multireference configuration interaction approach. The transition dipole moments between these states are computed. To calculate the potential energy curves accurately, core-valence correlation and scalar relativistic corrections are accounted for and the extrapolation of the potential energies to the complete basis set limit is included. The rotationless radiative lifetimes are of the order of 10 ns for all vibrational levels of the A 1 Π and E 1 Σ + states, suggesting that spontaneous vibronic emissions originating from the two states occur easily. The band origins, Einstein A coefficients, and Franck–Condon factors of all the vibronic emissions are calculated. Overall, the Einstein A coefficients of numerous spontaneous emissions from the A 1 Π–X 1 Σ + and E 1 Σ + –X 1 Σ + systems are large, suggesting that these vibronic emissions are strong and therefore easy to measure through spectroscopy. The Einstein A coefficients of all the vibronic emissions from the E 1 Σ + –A 1 Π system are small, predicting that the E 1 Σ + –A 1 Π transition is weak and therefore difficult to detect through experiment, regardless of the total radiative lifetimes of the E 1 Σ + state. The distribution of radiative lifetime with the variation of the rotational quantum number J is discussed briefly for the υ  ≤ 15 and J  ≤ 30 levels of the A 1 Π and E 1 Σ + states. At a certain υ, the radiative lifetime slowly increases as the J increases for the A 1 Π state, whereas it is almost constant for any J of the E 1 Σ + state. Graphical abstract: The PECs are calculated for the X 1 Σ +, A 1 Π, C 1 Σ −, D 1 Δ, and E 1 Σ + states of the SiO and the TDMs of the transitions between them are computed. The radiative lifetimes are of the order of 10 ns for all vibrational levels of the A 1 Π and E 1 Σ + states, suggesting that the vibronic emissions arising from the A 1 Π and E 1 Σ + states occur easily. Overall, the A 1 Π–X 1 Σ + and E 1 Σ + –X 1 Σ + transitions are strong, whereas the E 1 Σ + –A 1 Π transition is weak. The distribution of the radiative lifetime with the variation of the J is discussed for the υ  ≤ 15 and J  ≤ 30 levels of the A 1 Π and E 1 Σ + states. At a certain υ, the radiative lifetime gradually increases as the J increases for the A 1 Π state, whereas it is almost constant for any J of the E 1 Σ + state.Image, graphical abstract